Dream Team : a Practical Playbook to Help Innovative Educators Change Schools. - Tait, Aaron (Association for Supervision & Curriculum Development, 2018)
Rising international education leaders Tait and Faulkner offer audacious insight, lots of practical tools, and an experience-proven process to guide school-based teams pursuing bold change.